Formulation and evaluation of sublingual tablets containing Sumatriptan succinate - Prajapati, Shailesh T; Patel, Parth B; Patel, Chhagan N (International Journal of Pharmaceutical Investigation)
Objective: Sumatriptan succinate is a selective 5-hydroxytryptamine-1 receptor agonist effective in the acute treatment of migraine headaches, having low bioavailability of about 15% orally due to first-pass metabolism. The purpose of this research was to mask the intensely bitter taste of Sumatriptan succinate and to formulate fast-acting, taste-masked sublingual tablet formulation. Materials and Methods: Taste masking was performed by solid dispersion method with mannitol and ion exchange with Kyron T 114 because it releases the drug in salivary pH. The resultant batches were evaluated for in-vivo taste masking as well compatability study (Fourier transform infrared (FTIR) and differential scanning calorimetry (DSC)). For a better feel in the mouth, menthol and sweetener Na saccharine were added to the tablet formulation. The tablets were prepared by direct compression and evaluated for weight variation, thickness, friability, drug content, hardness, disintegration time, wetting time, in vitro drug release, and in vitro permeation study. Resuts and Discusion: Optimized batches disintegrated in vitro within 28-34 s. Maximum drug release could be achieved with in 10 min for the solid dispersion batches and 14-15 min for the ion-exchange batches with Kyron T 114. The optimized tablet formulation showed better taste and the formulated sublingual tablets may act as a potential alternate for the Sumatriptan succinate oral tablet. Conclusion: Sumatriptan succinate can be successfully taste-masked by both the solid dispersion method using mannitol by the melting method and Ion exchange resin with Kyron T114. It was also concluded that prepared formulation improve bioavailability by prevention of first pass metabolism.
Keywords: Ion-exchange resin Kyron T 114; mannitol; solid dispersion; taste masking